STRATEGI KOMUNIKASI PEMBELAJARAN BAHASA INGGRIS UNTUK MENINGKATKAN KEMAMPUAN BAHASA DI KAMPUNG INGGRIS DESA BERINGIN KABUPATEN KUANTAN SINGINGI - Leora Gusita; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Education is a very important element to create quality human resources. British village be in a village as a faster alternative school for her student the English language. Learning is done every day of the week starting from morning till night for six months more quickly proven to help her improve their language skills. By using the communication strategy learning in teaching and learning in the English village. The purpose of this study was to determine the learning strategies used in the English village, teacher communication process with the students in learning English, and know the communication media used in teaching and learning in English village.This study uses qualitative research methods with the presentation of analysis desktriptif. The informants are teachers as lecturers and students of English villages were selected purposively. Data collection techniques used were observation, interviews, and documentation. The validity of the technique used in this research is triangulation and extension of participation.The results obtained show that learning strategies English teacher in the village using ekspositorik and heuristic strategies, learning strategies also helped by using teaching methods such as exercise method and method of administration tasks. The communication process is done by teachers and students see the opportunities then sets objectivity and create an alternative strategy, then implement these strategies in the learning process and the final evaluation of what has been done and compared with the previous plan drawn up. The communication media used in the English village using media tools, audio media and audio-visual media in petrified improve English language skills in English village Beringin villageKeywords : Communication Strategy, English Village, Kabupaten Kuantan Singingi